Hand hygiene during facility-based childbirth in Cambodia: a theory-driven, mixed-methods observational study - Yolisa Nalule; Helen Buxton; Por Ir; Supheap Leang; Alison Macintyre; Ponnary Pors; Channa Samol; Robert Dreibelbis (BMC, 2021)
Abstract Background Despite current efforts to improve hand hygiene in health care facilities, compliance among birth attendants remains low. Current improvement strategies are inadequate, largely focusing on a limited set of known behavioural determinants or addressing hand hygiene as part of a generalized set of hygiene behaviours. To inform the design of a facility -based hand hygiene behaviour change intervention in Kampong Chhnang, Cambodia, a theory-driven formative research study was conducted to investigate the context specific behaviours and determinants of handwashing during labour and delivery among birth attendants. Methods This formative mixed-methods research followed a sequential explanatory design and was conducted across eight healthcare facilities. The hand hygiene practices of all birth attendants present during the labour and delivery of 45 women were directly observed and compliance with hand hygiene protocols assessed in analysis. Semi-structured, interactive interviews were subsequently conducted with 20 key healthcare workers to explore the corresponding cognitive, emotional, and environmental drivers of hand hygiene behaviours. Results Birth attendants' compliance with hand hygiene protocol was 18% prior to performing labour, delivery and newborn aftercare procedures. Hand hygiene compliance did not differ by facility type or attendants' qualification, but differed by shift with adequate hand hygiene less likely to be observed during the night shift (p = 0.03). The midwives' hand hygiene practices were influenced by cognitive, psychological, environmental and contextual factors including habits, gloving norms, time, workload, inadequate knowledge and infection risk perception. Conclusion The resulting insights from formative research suggest a multi-component improvement intervention that addresses the different key behaviour determinants to be designed for the labour and delivery room. A combination of disruption of the physical environment via nudges and cues, participatory education to the midwives and the promotion of new norms using social influence and affiliation may increase the birth attendants' hand hygiene compliance in our study settings.